Compliance to kangaroo mother care best practice: an evidence-based implementation project. Issue 3 (5th September 2021) - Siraneh, Yibeltal; Berhane, Melkamu; Abraham, Gelila; Feyissa, Garumma Tolu; Morankar, Sudhakar
ABSTRACT: Background: Worldwide about 13 million babies are born prematurely every year. Kangaroo mother care (KMC) is a proven, acceptable and feasible method to decrease the mortality rate of premature infants. Reviewing current KMC practices, implementing in the context and auditing the compliance would benefit the promotion evidence-based practice (EBP), which was not well known in the study area. Objectives: The main objective of the study was to increase awareness of EBP for KMC in the neonatal care unit of a public hospital through identifying local barriers and facilitators, and to measure compliance with best practice recommendations. Methods: The current KMC best practice quality improvement project was conducted between March and May 2018. The project team was established for this implementation project. Six KMC best practice audit criteria were used to evaluate the compliance at baseline and endline using the Joanna Briggs Institute Practical Application of Clinical Evidence System and Getting Research into Practice audit and feedback tool. All (20) clinical staff who were working in the neonatal care unit were included in the study. Based on the baseline audit result, gaps and barriers were identified and discussed, and implementation strategies specific to the local setting were developed to mitigate the gaps. Baseline results were compared with the final follow-up audit result to measure change in compliance. Again, these data were compared with other studies to identify the sustainability of the project in a clinical setting. Results: A total of 80 cases (baseline 20 and implementation 60) were observed demonstrating KMC procedures. Study found that follow-up compliance rates for all criteria improved compared with baseline audit; for example, criterion 5 (assessment of infant's condition) improved from 20% during baseline to 90% during follow-up and criterion 3 (parent/family received counselling) improved from 30 to 95%. Conclusion: The current study demonstrated that EBP training and frequent supportive supervision translated in improved compliance to best available evidence to KMC in a resource-limited setting.